MXene-Based Composites as Nanozymes in Biomedicine: A Perspective - Siavash Iravani; Rajender S. Varma (Nano-Micro Letters, 2022)
Abstract MXene-based nanozymes have garnered considerable attention because of their potential environmental and biomedical applications. These materials encompass alluring and manageable catalytic performances and physicochemical features, which make them suitable as (bio)sensors with high selectivity/sensitivity and efficiency. MXene-based structures with suitable electrical conductivity, biocompatibility, large surface area, optical/magnetic properties, and thermal/mechanical features can be applied in designing innovative nanozymes with area-dependent electrocatalytic performances. Despite the advances made, there is still a long way to deploy MXene-based nanozymes, especially in medical and healthcare applications; limitations pertaining the peroxidase-like activity and sensitivity/selectivity may restrict further practical applications of pristine MXenes. Thus, developing an efficient surface engineering tactic is still required to fabricate multifunctional MXene-based nanozymes with excellent activity. To obtain MXene-based nanozymes with unique physicochemical features and high stability, some crucial steps such as hybridization and modification ought to be performed. Notably, (nano)toxicological and long-term biosafety analyses along with clinical translation studies still need to be comprehensively addressed. Although very limited reports exist pertaining to the biomedical potentials of MXene-based nanozymes, the future explorations should transition toward the extensive research and detailed analyses to realize additional potentials of these structures in biomedicine with a focus on clinical and industrial aspects. In this perspective, therapeutic, diagnostic, and theranostic applications of MXene-based nanozymes are deliberated with a focus on future perspectives toward more successful clinical translational studies. The current state-of-the-art biomedical advances in the use of MXene-based nanozymes, as well as their developmental challenges and future prospects are also highlighted. In view of the fascinating properties of MXene-based nanozymes, these materials can open significant new opportunities in the future of bio- and nanomedicine.